A Qualitative Examination of the Factors related to the Development and Maintenance of Insomnia in Cancer Survivors - Garland, Sheila N. (Palliat Support Care, 2018)
OBJECTIVE: Insomnia is under recognized and inadequately managed with close to 60% of cancer survivors experiencing insomnia at some point in the treatment trajectory. The objective of this study was to further understand predisposing, precipitating and perpetuating factors in the development and maintenance of insomnia in cancer survivors. METHODS: A heterogeneous sample of 63 patients who had completed active treatment were recruited. Participants were required to have a score >7 on the Insomnia Severity Index and meet the diagnostic criteria for insomnia disorder. Open-ended, semi-structured interviews were conducted to elicit participants’ experiences with sleep problems. An a priori set of codes and a set of codes that emerged from the data were used to analyze the data. RESULTS: The mean age of the sample was 60.5 years, with 30% identifying as non-white and 59% reporting their sex as female. The cancer types represented was heterogeneous with the two most common being breast (30%) and prostate (21%). Participants described an inherited risk for insomnia, anxious temperament, and insufficient ability to relax as predisposing factors. Respondents were split as to whether they classified their cancer diagnosis as the precipitating factor for their insomnia. Participants reported several behaviors that are known to perpetuate problems with sleep including napping, using back-lit electronics before bed, and poor sleep hygiene. One of the most prominent themes identified was the use of sleeping medications. Participants reported that they were reluctant to take medication but felt that it was the only option to treat their insomnia and that it was encouraged by their doctors. SIGNIFICANCE OF RESULTS: Insomnia is a prevalent, but highly treatable, disorder in cancer survivors. Patients and provider education is needed to change individual and organizational behaviors that contribute to the development and maintenance of insomnia and increase access to evidence-based nonpharmacological interventions.